Chlorinated Phospholipids and Fatty Acids: (Patho)physiological Relevance, Potential Toxicity, and Analysis of Lipid Chlorohydrins - Schröter, Jenny (Oxid Med Cell Longev, 2016)
Chlorinated phospholipids are formed by the reaction of hypochlorous acid (HOCl), generated by the enzyme myeloperoxidase under inflammatory conditions, and the unsaturated fatty acyl residues or the head group. In the first case the generated chlorohydrins are both proinflammatory and cytotoxic, thus having a significant impact on the structures of biomembranes. The latter case leads to chloramines, the properties of which are by far less well understood. Since HOCl is also widely used as a disinfecting and antibacterial agent in medicinal, industrial, and domestic applications, it may represent an additional source of danger in the case of abuse or mishandling. This review discusses the reaction behavior of in vivo generated HOCl and biomolecules like DNA, proteins, and carbohydrates but will focus on phospholipids. Not only the beneficial and pathological (toxic) effects of chlorinated lipids but also the importance of these chlorinated species is discussed. Some selected cleavage products of (chlorinated) phospholipids and plasmalogens such as lysophospholipids, (chlorinated) free fatty acids and α-chloro fatty aldehydes, which are all well known to massively contribute to inflammatory diseases associated with oxidative stress, will be also discussed. Finally, common analytical methods to study these compounds will be reviewed with focus on mass spectrometric techniques.